2023
DOI: 10.1177/02560909231166498
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disorders, Dispositional Mindfulness, and Mediating Role of Acceptance in Undergraduate and Postgraduate Students

Abstract: ‘For after all, the best thing one can do when it is raining is, let it rain.’ (Longfellow, 1906) Mental health conditions, including depression, anxiety, and stress, affect a sizable proportion of university students. Yet, little is known regarding the incidence of mental health issues among Indian university students. These mental health issues are generally caused by a range of factors, including academic demands, interpersonal connections (Steptoe, 2007), future prospects, competitive exams, peer pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…The studies done on such students reported a reduction in stress and an improvement in the mood of students due to mindfulness (O’Driscoll et al, 2017). Limited studies have been conducted on Indian students usually using MAAS (Bajaj & Pande, 2016; Bajaj et al, 2019; Benada & Chowdhry, 2017; V. Gupta & Sinha, 2023; Parajuli et al, 2023; Patel et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies done on such students reported a reduction in stress and an improvement in the mood of students due to mindfulness (O’Driscoll et al, 2017). Limited studies have been conducted on Indian students usually using MAAS (Bajaj & Pande, 2016; Bajaj et al, 2019; Benada & Chowdhry, 2017; V. Gupta & Sinha, 2023; Parajuli et al, 2023; Patel et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%